(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
The capability of determination of gender from unknown human skeletal remains is indispensable and the techniques to find out this from different bones of human skeletal remains have been researched tremendously. Several investigators have asserted the necessity for population specific statistical data for methods that are dependent on specific measurements as there exist ample variations in body size among diverse ethnic populations. Most reliable bone exhibiting sexual dimorphism in human body is the pelvis and we have chosen it for derivation of population and sex specific data with respect to diameter of acetabulum and acetabulopubic index. 72 adult, dry innominate hip bones without any morphological deformities and defects (38 of male and 34 of female sex) belonging to South Indian population were carefully studied with respect to diameter of Right acetabulum and acetabulopubic index derived from the maximum distance between pubis symphysis and the anterior rim of acetabulum i.e. cotylopubic length or acetabulum-pubis symphysis length. All measurements were accurately taken with the aid of digital Vernier caliper and results were analyzed by means of SPSS software version 26 and the results including the demarking point, standard deviation, sectioning point etc. were found to be statistically significant and therefore acetabulum diameter and acetabulopubic index can be authentically applied for sex determination from dry adult hip bones belonging to the South Indian population. From the analysis of demarking point, AP index of >94.13 identified 73.84% of male sex and <87.15 identified 84.97% of females and therefore AP index can definitely be considered as the positive and decisive indicator for sex determination from adult hip bones.